2014
DOI: 10.1007/s00268-014-2858-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lipid‐Modifying Therapy on Long‐Term Mortality After Abdominal Aortic Aneurysm Repair: A Systemic Review and Meta‐Analysis

Abstract: Meta-analysis of studies supports a protective role of lipid-modifying therapy on mortality risk after AAA repair. Aggressive lipid intervention should be recommended to those who receiving AAA repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 48 publications
0
8
0
1
Order By: Relevance
“…angiotensin converting enzyme inhibitors, beta blocking agents), lipid modifying therapy (i.e. statins), and antiplatelets 485,183,[486][487][488] although evidence about single drugs may be conflicting 489,490 . Applicable guidelines should be consulted for specific guidance on which atherosclerotic manifestation warrants which secondary prophylaxis.…”
Section: Medical Management After Aaa Repairmentioning
confidence: 99%
“…angiotensin converting enzyme inhibitors, beta blocking agents), lipid modifying therapy (i.e. statins), and antiplatelets 485,183,[486][487][488] although evidence about single drugs may be conflicting 489,490 . Applicable guidelines should be consulted for specific guidance on which atherosclerotic manifestation warrants which secondary prophylaxis.…”
Section: Medical Management After Aaa Repairmentioning
confidence: 99%
“…Similarly, Kaye et al [35] found that if the levels of HDL are insufficient, cholesterol and lipids in arterial walls trigger an exacerbated inflammatory response. Meta-analysis reported that low serum lipids may reduce patient mortality after abdominal aortic aneurysm repair [13]. Overall, increased TG/HDLc ratio in type B AAD is associated with aortic stiffness, inflammatory factors, and oxidative stress.…”
Section: Discussionmentioning
confidence: 98%
“…To date, dyslipidemia is a well-documented risk factor for stroke [8,9], metabolic syndrome [10], and cardiovascular disease [11,12]. Moreover, results from a meta-analysis suggested that lipid-modifying therapy is a protective factor on mortality after abdominal aortic aneurysm repair [13]. A cross-sectional study implicated dyslipidemia aortic stiffness [14], with international guidelines stating that lipid profiles should be managed [15].…”
Section: Introductionmentioning
confidence: 99%
“…As estatinas sãο drοgas que têm sidο bastante usadas para ο gerenciamentο de dοenças cardiοvascular. A influência das estatinas nο AAA é múltipla, pοis prοmοve a supressãο da inflamaçãο e remοdelaçãο da matriz extracelular, além de sua capacidade hipοlipidêmica (Salata et al, 2018;Zhang et al, 2015).…”
Section: Touma Et Al 2021unclassified